A review of unmanned surface vehicle for water quality assessment application - Zahari N.M.; Sankar P.; Ismail I.N.; Zawawi M.H.; Nashrudin M.N.; Aziz N.A.; Nurhikmah F. (American Institute of Physics, 2025)
With increased global interest in commercial and scientific concerns related to both oceans, there has been an increase in demand for the development of unmanned surface vehicles (USVs). Water monitoring technology has significantly improved the efficiency of water resource management. Stationary and portable water quality monitoring, as well as a movable surface vehicle, have expanded the use of on-site water measurements and monitoring in recent years. Traditional water measuring methods, which are usually carried out in laboratories, can only go so far in assisting decision-making in a timely and informed manner. This paper provides a comprehensive study of recent advancements in the application of Unmanned Surface Vehicles (USVs). A new method and components have been approached for water quality monitoring which is called Water Sensor Network that combines wireless waters sensor technology with Unmanned Surface Vehicle (USV). The USV consists of water quality sensors, a wireless communication system, and a mobility platform. ? 2024 Author(s).